1993
DOI: 10.2307/2328923
|View full text |Cite
|
Sign up to set email alerts
|

Options, Short Sales, and Market Completeness

Abstract: This paper presents empirical evidence that trading in options contributes to both transactional and informational efficiency of the stock market by reducing the effect of constraints on short sales. The significantly higher average level of short interest exhibited by optionable stocks supports the argument that options facilitate short selling. We also find significant effects on option prices, related to the short interest in the underlying stock. We then present evidence that options also increase informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
176
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(183 citation statements)
references
References 1 publication
7
176
0
Order By: Relevance
“…Most previous studies have used monthly stock-specific short interest data (e.g., Figlewski and Webb (1993), Figlewski (1981), Dechow, Hutton, Meulbroek, and Sloan (2001), Desai et al (2002), Asquith, Pathak, and Ritter (2005), and Singal and Xu (2005)). There are three important problems with using monthly short interest data.…”
mentioning
confidence: 99%
“…Most previous studies have used monthly stock-specific short interest data (e.g., Figlewski and Webb (1993), Figlewski (1981), Dechow, Hutton, Meulbroek, and Sloan (2001), Desai et al (2002), Asquith, Pathak, and Ritter (2005), and Singal and Xu (2005)). There are three important problems with using monthly short interest data.…”
mentioning
confidence: 99%
“…Figlewski (1981) finds a significant negative relationship between risky asset returns and short interest, with the latter used as a proxy for the amount of negative information which would otherwise results in short sales were there no restrictions. Repeating the same tests on another period, Figlewski and Webb (1993) still show the relationship to be negative, albeit non-significant. The use of the recorded short interest as a proxy for the amount of adverse information excluded from the market price requires that observed short positions be proportional to short sales to be undertaken in the absence of restrictions.…”
mentioning
confidence: 82%
“…The empirical studies showed that the increases in short interest or short volume lead to the declines in stock returns (Diether et al, 2009a;Dehow et al, 2001;Asquith and 3) A large body of literature examines the effect of shorting on the shorted stock, except one paper (Hwang et al, 2017). Meulbroek, 1996;Conrad, 1994;Figlewski and Webb, 1993;Senchack and Starks, 1993). Academics also have studied the effect of the short-selling constraints on the asset prices.…”
Section: The Literature Reviewmentioning
confidence: 99%